Remote Learning, Academic Stress and Mental Health of Learners - CHAUHAN, ANAMIKA (JOURNAL OF INDIAN EDUCATION, 2025)
This comprehensive review explores the psychological consequences of remote learning on students’ mental health, with a focus on the broader implications of remote education beyond the context of COVID-19. Drawing from established psychological theories, the review highlights the challenges students face in remote learning environments. It identifies isolation and loneliness as key factors affecting emotional well-being, increased screen time as a contributor to psychological stress and the absence of traditional social interactions impacting social well-being. The review emphasises the importance of recognising and addressing these challenges, and provides strategies to foster mental health support, social connectedness and proactive self-regulation in remote learning. It concludes by advocating for a holistic approach to education that prioritises both academic success and the well-being of students in remote learning environments.